Untangling the oxidative cost of reproduction: An analysis in wild banded mongooses. Issue 3 (8th March 2022) - Meniri, Magali; Evans, Elsa; Thompson, Faye J.; Marshall, Harry H.; Nichols, Hazel J.; Lewis, Gina; Holt, Lauren; Davey, Emma; Mitchell, Christopher; Johnstone, Rufus A.; Cant, Michael A.; Blount, Jonathan D.
Abstract: The cost of reproduction plays a central role in evolutionary theory, but the identity of the underlying mechanisms remains a puzzle. Oxidative stress has been hypothesized to be a proximate mechanism that may explain the cost of reproduction. We examine three pathways by which oxidative stress could shape reproduction. The "oxidative cost" hypothesis proposes that reproductive effort generates oxidative stress, while the "oxidative constraint" and "oxidative shielding" hypotheses suggest that mothers mitigate such costs through reducing reproductive effort or by pre‐emptively decreasing damage levels, respectively. We tested these three mechanisms using data from a long‐term food provisioning experiment on wild female banded mongooses ( Mungos mungo ). Our results show that maternal supplementation did not influence oxidative stress levels, or the production and survival of offspring. However, we found that two of the oxidative mechanisms co‐occur during reproduction. There was evidence of an oxidative challenge associated with reproduction that mothers attempted to mitigate by reducing damage levels during breeding. This mitigation is likely to be of crucial importance, as long‐term offspring survival was negatively impacted by maternal oxidative stress. This study demonstrates the value of longitudinal studies of wild animals in order to highlight the interconnected oxidative mechanisms that shape the cost of reproduction. Abstract : The cost of reproduction plays a central role in evolutionary theory, but the identity of the underlying mechanisms remains a puzzle. Oxidative stress has been hypothesized to be a proximate mechanism that may explain the cost of reproduction. We examine three pathways by which oxidative stress could shape reproduction using data from a long‐term food provisioning experiment on wild female banded mongooses ( Mungos mungo ).